A web-based tool for synthesis assessments of the impacts of climate change on water resources. (November 2020) - Borges de Amorim, Pablo; Silva de Souza, Kleber Isaac; Borges Chaffe, Pedro Luiz
Abstract: The impact of climate change on water resources is one of the major challenges of our society. Synthesis work is essential to tackle these challenges in a scientifically sound way. Synthesis assessments can benefit from interactive web applications that allow easy access, managing, and updating of its database. We developed a web-based tool for the synthesis assessment of the impacts of climate change on the water resources of Brazil. The tool, called YARA, allows users to interact with the literature database and extract information of interest, all in an updatable fashion. YARA was tested by 107 stakeholders and several improvements were suggested and implemented, such as an interactive table and a form for registering new studies. The survey confirmed the value of YARA and we believe the tool is an important step to support robust adaptation strategies towards a more resilient society. Highlights: We developed a web-based synthesis tool that allows users to extract specific information within an updatable database. The tool is useful for literature reviews and national assessments on the impacts of climate change on water resources. More than a hundred stakeholders tested the tool and the vast majority found it useful.